Kompetensi Guru Pendidikan Agama Kristen di Era Society 5,0 - Wassar, Sarah; Indriati Tjipto Purnomo; Ipan Morris Pangaribuan; Simon Simare Mare; Stefanus Alpha Yani Kristiono (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
Educators or teachers who are in the era of society 5.0 must take advantage of these three things, namely: Internet of things in the world of education (IoT), Virtual/Augmented reality in the world of education, and the use of Artificial Intelligence (AI) to find out and identify the learning needs needed by students. "With so many changes in technology, can teacher competence be replaced by technology? The aim of this research is to describe the competency of Christian Education teachers in dealing with educational technology in the Society 5.0 era. And especially for the competence of Christian Education teachers who are creative and innovative, quality and relevant to the needs of the times. This research uses qualitative methods in the form of descriptive analysis. The analysis used by researchers to assess the competence of t Christian Education eachers indirectly. There are teacher competencies that do not exist in the technological era, such as direct interaction in the classroom, emotional relationships between teachers and students, character development, life values ​​and a teacher's example. In particular, the competencies of Christian Education teachers that do not exist in the Society 5.0 era are personality competencies, social competencies and pedagogical competencies. Based on the research results, it is recommended that in facing the era of society 5.0, Christian Education teachers continue to have and develop good personality, pedagogical and social competencies, becoming an inspiration for students' affective and creative growth. Transform into a competent and tough teacher.